Barriers and facilitators to the implementation of workplace health promotion programs: Employers' perceptions - Campmans, Jennifer M. D.; Smit, Denise J. M.; van Oostrom, Sandra H.; Engels, Josephine A.; Proper, Karin I. (Frontiers in Public Health, 2023)
Background Workplace health promotion programs (WHPPs) can benefit the lifestyle and health of employees. However, not all WHPPs have been successful in their implementation, and thus their effectiveness. This study aimed to identify the barriers and facilitators to implementing an integrated WHPP, which targets multiple lifestyle factors at different levels (individual and organizational), from an employer's perspective. Methods Data were collected by two online focus groups among 18 representatives of eight different organizations. Data from the focus group discussions were transcribed verbatim and analyzed using thematic analysis. Data were coded both inductively and deductively, using the Consolidated Framework for Implementation Research (CFIR) consisting of the following five domains: (1) intervention characteristics, (2) outer setting, (3) inner setting, (4) characteristics of individuals, and (5) process. Ratings were performed to indicate the positive or negative influence and strength of a construct regarding the implementation of WHPPs. Results Barriers and facilitators in all domains of the CFIR were found. Regarding characteristics of the WHPP, complexity and costs hindered implementation, while high adaptability facilitated it. An organization that met the needs of employees (the outer setting) facilitated implementation. Available resources, access to knowledge, leadership involvement, and continuity of communication were facilitators within the inner setting. Barriers were different approaches to implementation within one organization and the perceived interference with employees' lives. For the implementation process, the involvement of key stakeholders, including employees, was identified as an important facilitator. Conclusion Various barriers and facilitators in different domains play a role in the implementation of integrated WHPPs, according to employers. Strategies that tackle the identified barriers and incorporate the facilitators will likely contribute to the successful implementation of integrated WHPPs.